DEVELOPMENT OF ELEMENTS OF ENVIRONMENTALLY SAFE TECHNOLOGY OF WHITE CABBAGE PROTECTION - Z.-G. S. Shibzukhov; M. I. Eziev; A. A. Zherukova; Z. S. Shibzukhova (Новые технологии)
Biological preparations should be used as an alternative to chemical preparations to protect crops from pests for effective and environmentally friendly cultivation of white cabbage plants in the south of Russia. When developing new technologies for growing vegetable products, entomopathogenic nematodes, which act as effective protection of vegetable crops from pests, have increasingly been used. When they are applied many researchers get environmentally friendly products with increased yields up to 35-40 %.In the conditions of the KBR the number of Lepidoptera caterpillars often exceeds the threshold level of safety, thereby forcing farmers to resort to immediate treatment with fast-acting drugs to save the yield of white cabbage. In this regard, Lepidocide was tested as one of the most promising and the most safe and effective remedy of all Russian preparations containing endoxin. The widely used Decis expert preparation has many negative properties, including environmental pollution and reduced environmental friendliness of the products. And also, as practice shows, it is not always effective in arid regions where white cabbage is cultivated.During white cabbage harvesting the plants are quite resistant to pests, however, with their mass distribution, the marketability of the cabbage worsens significantly, and in order to maintain environmental standards it is necessary to use biological products that can effectively cope with the pests by reducing their numbers. It was experimentally proved that the use of Lepidocide preparation during the experiments allowed to obtain high-quality products. Lepidocide was also used in studies to reduce the number of caterpillars of cabbage butterfly. Studies showed that they were less susceptible to the effects of Lepidocide. When assessing the yield a significant increase in the experience was not noted. In the version without the use of preparations (water), this indicator amounted to 4.22 t/ha, in the version with Decis expert, CE – 4.53 t/ha, when treated with Lepidocide – 4.48 t/ha